Ancient landscape evolution tracked through cosmogenic krypton in detrital zircon - Maximilian Dröllner; Milo Barham; Christopher L. Kirkland; Taryn Scharf; Sabrina Niemeyer; Tibor J. Dunai (Proceedings of the National Academy of Sciences, 2026)
Cosmogenic nuclides have revolutionized our quantitative understanding of landscape evolution via measurements of near-surface erosion, exposure, and burial. Here, we integrate stable cosmogenic krypton in detrital zircon with U–Pb geochronology to extend the temporal limits of cosmogenic nuclide applications and reconstruct Eocene landscape evolution from drill cores of placer deposits in southern Australia. Zircon U–Pb crystallization ages are interpreted to reflect paleodrainage from a deeply weathered ~800,000 km 2 hinterland and transport via a ~1,000 km littoral drift system. The measured cosmogenic 78 Kr concentration of detrital zircon samples ranges from ~6.4 × 10 5 to 1.8 × 10 7 atoms per gram, suggesting low paleodenudation rates of 0.3 to 0.7 m per My [interquartile range (IQR)]. Such low denudation rates are below those expected by comparison to modern analogs and point to underestimation due to re-exposure during sediment transport and shallow storage. Expressing the concentrations as apparent exposure times, which approximate the near-surface integrated residence time, yields estimates of 0.9 to 2.1 My (IQR). In the stratigraphic and mineralogical context, the dataset records a shift from compositionally mature placers with uniformly high residence times (~1.6 My) to less mature placers with stratigraphically variable residence times (~0.7 to 2.7 My). We infer a shift from prolonged sediment storage, during which the mineral assemblage was modified, to a more dynamic transport regime with higher net transfer rates. The timing suggests eustatic and tectonic forcing, and cosmogenic krypton captures this transition, aiding reconstruction of how ancient landscapes and the sedimentary record coevolve.